Functional coupling of presequence processing and degradation in human mitochondria. (3rd June 2020) - Kücükköse, Cansu; Taskin, Asli Aras; Marada, Adinarayana; Brummer, Tilman; Dennerlein, Sven; Vögtle, Friederike‐Nora
Abstract : The mitochondrial proteome is built and maintained mainly by import of nuclear‐encoded precursor proteins. Most of these precursors use N‐terminal presequences as targeting signals that are removed by mitochondrial matrix proteases. The essential mitochondrial processing protease MPP cleaves presequences after import into the organelle thereby enabling protein folding and functionality. The cleaved presequences are subsequently degraded by peptidases. While most of these processes have been discovered in yeast, characterization of the human enzymes is still scarce. As the matrix presequence peptidase PreP has been reported to play a role in Alzheimer's disease, analysis of impaired peptide turnover in human cells is of huge interest. Here, we report the characterization of HEK293T PreP knockout cells. Loss of PreP causes severe defects in oxidative phosphorylation and changes in nuclear expression of stress response marker genes. The mitochondrial defects upon lack of PreP result from the accumulation of presequence peptides that trigger feedback inhibition of MPP and accumulation of nonprocessed precursor proteins. Also, the mitochondrial intermediate peptidase MIP that cleaves eight residues from a subset of precursors after MPP processing is compromised upon loss of PreP suggesting that PreP also degrades MIP generated octapeptides. Investigation of the PreP R183Q patient mutation associated with neurological disorders revealed that the mutation destabilizes the protein making it susceptible to enhanced degradation and aggregation upon heat shock. Taken together, our data reveal a functional coupling between precursor processing by MPP and MIP and presequence degradation by PreP in human mitochondria that is crucial to maintain a functional organellar proteome. Abstract : Mitochondria build their proteome mainly through the import of cytosolic precursors with cleavable targeting signals that are removed by presequence proteases upon import. Kücükköse et al . show that the presequence peptidase PreP degrades cleaved targeting signals to prevent feedback inhibition of presequence processing in human mitochondria. The loss of PreP results in mitochondrial dysfunction and imbalanced proteostasis and triggers a nuclear transcriptional response.